Vegetation Structure and Tree Species Diversity inside and outside a Newly Established Zalon Taung National Park in Northwest Myanmar - Tin Hnaung Aye; Shozo Shibata (International Journal of Forestry Research)
The Zalon Taung National Park (ZNP) in Banmauk township, northwest Myanmar, is a recently established protected area to protect the area’s cultural value, ecosystems, native flora, and wildlife. This research examined the vegetation structure, tree species diversity, and composition within (ZNP) and outside (the Banmauk unclassified forest (BUCF)) the park to inform conservation and resource utilization for sustainable management. We conducted the vegetation survey in April-May of 2022 by setting up 34 sample plots (40 × 40 meters) using a random sampling approach. We used stand density, basal area, Shannon–Wiener diversity index, Simpson index, Pielou's evenness, Fisher’s α diversity, and Importance Value Index (IVI) to determine the forest structure and tree diversity. A total of 116 tree species (≥10 cm·dbh), representing 87 genera and 48 families, were identified. The ZNP sample plots had a slightly higher stand density (201 individuals ha−1) and basal area (20.6 m2·ha−1) than BUCF (stand density: 191 individuals ha−1 and basal area: 15.0 m2·ha−1), which is accessible to collect firewood and timber extraction by residents. The reverse J-shaped pattern of the population structure indicated that the stands’ populations were progressive and healthy. BUCF featured the most Verbenaceae (12.9%) and the ZNP the most Euphorbiaceae (7.2%) families. Protium serratum had the highest IVI in the BUCF (26.91%) and Dipterocarpus alatus (18.39%) in the ZNP. Dipterocarpus alatus and Dalbergia oliveri (IUCN Red List-endangered species) dominate in BUCF and require special attention in conservation planning. In the ZNP, previous logging activity dramatically reduced the relative density and the IVI values of commercially important species such as Tectona grandis, Dalbergia oliveri, and Protium serratum. According to the NMDS ordination, differences in tree species compositions were significantly linked with elevation, the intensity of logging, and distance to the village and road. The results will help park managers plan effective land use to promote biodiversity conservation and local livelihoods.